Awareness of deficit following traumatic brain injury: A systematic review of current methods of assessment. Issue 1 (2nd January 2021) - Brown, Laura; Fish, Jessica; Mograbi, Daniel C.; Bellesi, Giulia; Ashkan, Keyoumars; Morris, Robin
ABSTRACT: Background: Awareness of deficit plays an important role in adjustment following a brain injury and has been noted to impact on engagement with and outcome of rehabilitation. However, there are challenges associated with the assessment of awareness. Aim: To systematically review all instruments used to assess intellectual awareness of deficits following Traumatic Brain Injury (TBI) in adults, and evaluate instrument characteristics (e.g., the format and focus of measures of awareness) and assessment methods adopted. Results: Thirty-four studies, all rated as fair to good quality, were identified and within these twenty-three different assessment tools were adopted. The most common method of assessment was patient-proxy discrepancy, with three frequently used instruments employed in a total of 22 of the 34 studies. Across studies, variability was noted regarding the type of assessment method dependent on various sample demographics (e.g., age of sample) and injury characteristics (e.g., time post injury). Conclusions: There is no consensus on the preferred instrument to assess intellectual awareness of deficits after TBI. Continued instrument development should attempt to incorporate multiple perspectives and assessment should take into account demographic and injury-related factors. An insightful avenue for future research would be to determine which factors are likely to impact awareness measurement.